Towards innovative approaches for affordable housing in the gap market : a case study of Khayelitsha Township in Cape Town, South Africa - Muhoro, Gloria Nyawira (GSB: Faculty, 2016)
Post-apartheid South Africa has been criticized for failing to satisfactorily achieve its election promise of redistribution and poverty alleviation. While success has been noted in the provision of affordable housing and subsequently home ownership for lower income households, housing demand continue to far outstrip delivery capacity. Those excluded from homeownership include key public sector workers and laborers who face common, but divergent constraints. They are either too rich to qualify for housing subsidy, or too poor to afford homes in the prime market. They constitute the 'gap market'. Utilizing qualitative data from in-depth semi-structured interviews conducted with banks, property developers, government and residents in Khayelitsha (a state-subsidized housing settlement in the city of Cape Town), this thesis sought to understand the current challenges faced by the housing market in addressing the needs of the gap market in Cape Town, South Africa. The research identifies the major impediments to meeting the current housing demand in urban South Africa and points to new policy directions that could address the housing gap. Key findings indicate that the major obstacles to home ownership in the gap market include affordability constraints, over-indebtedness, poor credit ratings, and inadequate supply for this income bracket. While these obstacles show little indication of abating, this research's findings and recommendations suggest new pathways for formulating new housing policies that address the housing backlog in the gap market. This also suggests that government policies are critical in developing a healthy and inclusive housing market.